Localised pigmented villonodular synovitis of Hoffa’s fat pad- treatment using 70 degree arthroscope and superolateral portal: a case report - Magar, Sumedh H.; Magar, Hemant S. (International Journal of Research in Orthopaedics, 2019)
The localized form of pigmented villo-nodular synovitis (PVNS) is a rare pathological entity characterized by limited involvement of the synovium. The knee is the most commonly affected joint, and the disorder presents as a nodular, pedunculated lesion. The lesion usually presents as mechanical symptom such as locking of the knee. We report a case of localized PVNS that involved patellar fat pad an extremely rare area of involvement, previously described only in 4 cases, presenting as palpable mass. Complete excision of the lesion was performed through superolateral portal with use of 70-degree arthroscope. 70-degree arthroscope allows us to completely visualize infra-patellar region through superolateral portal and is recommended than 30-degree arthroscope for treatment of infra-patellar lesions. Patient was symptomless at 3 months follow up.